Biodiversity Contribution to Sustainable Development Goals in Indonesia - Tjitrosemito, Soekisman (SEAMEO BIOTROP, 2023)
In 2015, the world leaders agreed to the 17 Sustainable Development Goals (SDGs)- a shared blueprint for peace, prosperity for people, and the planet, now and into the future. These SDGs are 1. No poverty, 2. Zero hunger, 3. Good Health and Well-being, 4. Quality Education, 5. Gender Equality, 6. Clean Water and Sanitation, 7. Affordable and Clean Energy, 8. Decent work and Economic Growth, 9. Industry, Innovation and Infrastructure, 10. Reduced inequalities, 11. Sustainable cities and communities, 12. Responsible consumption and production, 13. Climate Action, 14. Life below Water, 15. Life on Land, 16. Peace, Justice, and Strong Institutions, 17. Partnership for the Goals, 17. Sustainable Development Goals Integration. In this article, we propose and highlight the rapid loss of biodiversity and dangerously changing climate are some indicators of this crisis.